Monitoring the Characteristics of High School Physics Learning Devices Refers to the 2013 Curriculum Content and Process Standards - M. Ibnusaputra; Jumadi Jumadi (Postgraduate, University of Mataram, 2022)
This research is a qualitative research method with the type of document analysis and supported by interview studies. The purpose of this study is to describe the characteristics of high school physics learning tools that reach the content standards and process standards of Curriculum 2013. The documents analyzed are in the form of high school physics learning tools soft files from four teachers as respondents from different schools. The selection of the teachers was carried out by purposive sampling and the learning device data were analyzed descriptively. The research step begins by asking each teacher for the same type of learning tools, consisting of lesson plans, student’s worksheet, and instrument test for daily exams. Supporting step is an interview study with a semi-open model. The results of the data analysis of learning devices there are still 2 teachers who do not meet these types of learning tools, and only 1 teacher in the aspect of learning time allocation does not reach the standard process, which is only 30 minutes. Then generally each teacher is still not able to achieve aspects of the standard content, namely the achievement of basic competencies